Effect of work environment, work discipline, work motivation, workload, and transformational leadership on performance of puskesmas employees - Julio Adi Bhaskara; Suranto Suranto; Ulung Pribadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to analyze the influence of the work environment, work discipline, work motivation, workload, and transformational leadership on employee performance at Puskesmas Magelang Regency. The descriptive quantitative method was used in this research. The number of samples is 8% of the employees of all Puskesmas, about 137 employees. Data collection technique used google form online questionnaire from October - November 2022. Data analysis using the Structural Equation Modelling Partial Least Square (SEM-PLS) technique with SmartPLS 3.0 Software analysis tool. This study found that work environment and work motivation significantly affected employee performance. Then, the workload and transformational leadership also significantly impact employee performance. Only work discipline did not have a significant effect on employee performance. The Four variables together significantly affect employee performance except for work discipline. Puskesmas leadership and other stakeholders need to pay attention to these four variables to increase the performance of Puskesmas employees, which will also affect Puskesmas performance.